Pregnancy outcome treated with stage-by-stage acupuncture and moxibustion therapy based on the chong channel being sea of blood theory in repeated IVF-ET failure patients: A randomized controlled trial. Issue 47 (20th November 2020) - Xing, Liwei; Xu, Jinlong; Zhang, Qiong; Li, Li; Li, Yunxiu; Zhuang, Haina; Yuan, Zhuojun; Zhao, Rong; Ma, Yanping
Abstract: Introduction: Acupuncture and moxibustion has become a commonly used adjuvant treatment method to improve the success rate of in vitro fertilization-embryo transfer (IVF-ET). However, There is still insufficient evidence that acupuncture treatment can improve the local microenvironment of endometrium, the endometrial receptivity, and the pregnancy outcome of patients, which is worthy of further study. Method/Design: To investigate the effect of Stage by Stage Acupuncture and Moxibustion Therapy on endometrial receptivity and Pregnancy Outcome based on the theory of "Chong channel being sea of blood, " we will conduct a multicenter randomized controlled trial. Inclusion criteria are as follows: infertile women under 45 years of age who received IVF-ET or Intracytoplasmic sperm injection cycles. The study will only be applied to women who have failed repeated implantation, that is, women who have failed 3 or more embryo transplants in the past (existing frozen embryos do not require the retrieval of eggs). Those who are not prepared to receive IVF-ET or are at risk of pregnancy, have a serious medical condition, or are egg donors will be excluded. Subjects will be randomly assigned to either the acupuncture group (IVF-ET plus stage-by-stage acupuncture and moxibustion therapy based on the "Chong channel being sea of blood" theory) or the control group (IVF-ET only). The trial required a total sample size of 246 women to compare endometrial receptivity between the 2 groups. The acupuncture group will receive acupuncture and moxibustion treatment 3 times a week starting from the third day of menstruation in the ovary stimulation cycle. One menstrual cycle was one course of treatment, and a total of 3 menstrual cycles were treated. The main outcome indicator was clinical pregnancy rate. Secondary outcome indicators were the three-dimensional volume blood flow parameters (vascularization index, flow index, and vascularization flow index) of the endometrium, endometrial thickness, endometrial volume, uterine artery PI, RI, and S/D during the "implantation window period" (20–24 days after menstruation in the ovary stimulation cycle). Discussion: This study will provide important evidence for the use of Stage by Stage Acupuncture and Moxibustion Therapy Based on the "Chong Channel Being Sea of Blood" Theory in IVF. Trial registration: http://www.chictr.org.cn/edit.aspx?pid=28811&htm=4 ID: ChiCTR1800017191 (07/17/2018).